Early life Triclosan exposure and child adiposity at 8 Years of age: a prospective cohort study - Geetika Kalloo; Antonia M. Calafat; Aimin Chen; Kimberly Yolton; Bruce P. Lanphear; Joseph M. Braun (BMC, 2018)
Abstract Background Triclosan is an antimicrobial agent that may affect the gut microbiome and endocrine system to influence adiposity. However, little data from prospective studies examining prenatal and childhood exposures exist. We investigated the relationship between multiple, prospective early life measure of triclosan exposure and child adiposity.  Methods In a prospective cohort of 220 mother-child pairs from Cincinnati, OH (enrolled 2003-2006), we quantified triclosan in urine samples collected twice during pregnancy, annually from 1 to 5 years of age, and once at 8 years. We assessed child adiposity at age 8 years using body mass index (BMI), waist circumference, and bioelectric impedance. We estimated covariate-adjusted associations of child adiposity with a 10-fold increase in average prenatal, average early childhood (average of 1-5 years), and 8-year triclosan concentrations. Results Among all children, there was no association between triclosan and child adiposity. While urinary triclosan concentrations at all three time periods were weakly, imprecisely, and inversely associated with all three measures of adiposity among girls, these associations did not differ significantly from those in boys (sex x triclosan p-values> 0.35). Among girls, the strongest associations were generally observed for prenatal triclosan when we adjusted for all three triclosan concentrations and covariates in the same model; BMI z-score (β: -0.13; 95% CI: -0.42, 0.15), waist circumference (β: − 1.7 cm; 95% CI: -4.2, 0.7), and percent body fat (β :-0.6; 95% CI: -2.7, 1.3). In contrast, the associations between triclosan concentrations and adiposity measures were inconsistent among boys. Conclusion We did not observe evidence of an association of repeated urinary triclosan concentrations during pregnancy and childhood with measures of child adiposity at age 8 years in this cohort.